Metagenomic Analysis of RNA Fraction Reveals the Diversity of Swine Oral Virome on South African Backyard Swine Farms in the uMgungundlovu District of KwaZulu-Natal Province - Ravendra P. Chauhan; James E. San; Michelle L. Gordon (Pathogens, 2022)
Numerous RNA viruses have been reported in backyard swine populations in various countries. In the absence of active disease surveillance, a persistent knowledge gap exists on the diversity of RNA viruses in South African backyard swine populations. This is the first study investigating the diversity of oral RNA virome of the backyard swine in South Africa. We used three samples of backyard swine oral secretion (saliva) collected from three distantly located backyard swine farms (BSFs) in the uMgungundlovu District, KwaZulu-Natal, South Africa. Total viral RNA was extracted and used for the library preparation for deep sequencing using the Illumina HiSeq X instrument. The FASTQ files containing paired-end reads were analyzed using Genome Detective v 1.135. The assembled nucleotide sequences were analyzed using the PhyML phylogenetic tree. The genome sequence analysis identified a high diversity of swine enteric viruses in the saliva samples obtained from BSF2 and BSF3, while only a few viruses were identified in the saliva obtained from BSF1. The swine enteric viruses belonged to various animal virus families; however, two fungal viruses, four plant viruses, and five unclassified RNA viruses were also identified. Specifically, viruses of the family Astroviridae, according to the number of reads, were the most prevalent. Of note, the genome sequences of Rotavirus A (RVA) and Rotavirus C (RVC) at BSF2 and RVC and Hepatitis E virus (HEV) at BSF3 were also obtained. The occurrence of various swine enteric viruses in swine saliva suggests a high risk of diarrhoeic diseases in the backyard swine. Of note, zoonotic viruses in swine saliva, such as RVA, RVC, and HEV, indicate a risk of zoonotic spillover to the exposed human populations. We recommend the implementation of biosecurity to ensure sustainable backyard swine farming while safeguarding public health.